2021
DOI: 10.1055/s-0041-1734361
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Chondromalacia Patella and Patellofemoral Factors in Middle-Age Population: A Clinical, Functional, and Radiological Analysis

Abstract: Background Despite higher incidence of patellofemoral pain (PFP) and consequently morbidity, the understanding about PF factors leading to PF arthritis is way lacking. Material and Methods A prospective study of first 80 patients who were diagnosed with chondromalacia patella (CMP) on magnetic resonance imaging (MRI) divided into early and late CMP groups were evaluated clinically, radiologically, and in terms of functional outcome. Results : Quadriceps angle, Clark’s test, and Insall–Salvati ratio results wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In a study in Chinese individuals, the trochlear groove angle was found 138.83 ± 4.77 degrees [20]. In the study by Kaur et al, in 80 patients who were diagnosed with chondromalacia patella on magnetic resonance imaging, Insall-Salvati index was found 1.2 and trochlear groove angle was found 153 degrees [22].…”
Section: Discussionmentioning
confidence: 92%
“…In a study in Chinese individuals, the trochlear groove angle was found 138.83 ± 4.77 degrees [20]. In the study by Kaur et al, in 80 patients who were diagnosed with chondromalacia patella on magnetic resonance imaging, Insall-Salvati index was found 1.2 and trochlear groove angle was found 153 degrees [22].…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, the factors affecting the stage of chondromalacia were trochlear morphological measurements, whereas there was no significant relationship between the IS index and patellar facet asymmetry. In a study investigating the chondromalacia stage and PFM morphology, it was reported that trochlear morphological measurements were associated with chondromalacia patella, but no significant correlation was found with the IS index (5). Similarly, Ali et al revealed that trochlear morphological measurements were associated with severe chondromalacia, but no correlation was found between patellar measurements and chondromalacia stage (1).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of the patella-another component of the joint-with the femur and patellar-shaped abnormalities may also affect the relationship with the joint. There are conflicting data regarding the effects of shape abnormalities of the structures forming the PF joint on patellar chondromalacia in the relevant literature (1,(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Arthroscopy is the gold standard for the diagnosis of patellar chondromalacia, but it is an invasive pro-Many studies in the literature have evaluated trochlear morphology and its relationship with chondromalacia patella using MRI [4][5][6][7][8][9][10] . Unlike the literature, we aimed to investigate the relationship between MRI measurements of both trochlear and patellar morphology and grade 3-4 patellar chondromalacia in our study.…”
Section: Introductionmentioning
confidence: 99%